Pembentukan Perilaku Peduli Lingkungan Hidup Desa Sitiaji Kabupaten Bojonegoro - Nindy Callista Elvania; Yenny Sri Margianti; Abilsa Duanda; Hesti Asriva; Bagus Saputra (Kreativasi : Journal of Community Empowerment, 2023)
Sitiaji Village is a village located far from the center of Bojonegoro City so that the village has never been socialized regarding environmental awareness by the relevant agencies. Even though currently the government of Bojonegoro Regency has implemented the "ADIBUANA" activity where Sitiaji Village is one of the villages that is required to participate in the program. This service aims to support the implementation of the "ADIBUANA" program in Bojonegoro Regency through the utilization of organic and inorganic waste. This service activity aims to analyze the needs and participation of the community with the method of applying science and technology. After socialization, the community has understood that waste can produce many benefits, for example by collecting organic waste in the surrounding environment to put it in biopore holes, which can later be used as fertilizer. Meanwhile, the use of inorganic waste, especially plastic waste, can be used as eco-bricks. After this service activity, the community is expected to be able to implement the adibuana program in the Sitiaji Village environment. Other community service activities must be carried out to strengthen people who care about the environment with joint activities such as mutual cooperation cleaning regularly, implementing better organic and inorganic waste management.